Doped and modified cathode materials and their preparation methods, lithium-ion batteries
Patent Information
- Application Number
- CN202610955076.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-30
- Publication Date
- 2026-09-01
AI Technical Summary
然而,简单的Ru掺杂未能针对表面氧释放最为剧烈的区域进行差异化强化,且均匀掺入的Ru在容量贡献和成本控制方面也带来额外负担
[0020]本申请提供的掺杂改性的正极材料中,Ru元素在富锂锰基正极材料的中心至表面均有分布,并且沿中心至表面的方向浓度递增。相关技术中Ru元素仅通过表面包覆层向近表面扩散、中心区域不含Ru或Ru浓度极低,或Ru元素在体相中均匀分布、各区域浓度趋同的情况,相比之下,本申请通过使Ru在中心和表面均有分布并形成由内至外的递增浓度梯度,利用Ru-O强共价键对晶格氧的锚定作用在颗粒不同区域形成差异化的功能协同:靠近中心的区域的低浓度Ru在维持层状结构骨架完整性的同时避免过度掺杂引起的晶格畸变,表面区域的高浓度Ru则在电化学循环过程中提供更强的氧锚定作用以减少表面晶格氧的不可逆释放。由此,本申请提供的掺杂改性的正极材料可充分利用其颗粒内部实现不同空间分区的功能协同,体现为中心低浓度维持结构、表面高浓度参与电荷补偿,进而有助于延缓富锂锰基正极材料在高电压循环过程中因不可逆相变和氧气逸出所引发的结构衰退,降低电压衰减和容量衰减的风险。同时,Ru在中心和表面的全域分布保证了梯度结构的完整性,有利于解决中心区域无Ru分布时内部结构支撑不足的问题。
Smart Images

Figure CN122677433A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of electrochemical energy storage technology, specifically to a doped and modified cathode material and its preparation method, and a lithium-ion battery. Background Technology
[0002] Lithium-rich layered oxide cathode materials (such as lithium-rich manganese-based cathode materials) have high specific capacity and energy density, and can be used in cathode systems for high-energy-density lithium-ion batteries. Unlike traditional materials that rely solely on the redox reaction of transition metals to provide capacity, the capacity of lithium-rich materials also comes from the reversible redox reaction of anions (lattice oxygen), and the resulting additional charge compensation gives them a higher specific capacity than similar materials.
[0003] However, while anionic redox contributes to capacity, it also causes severe structural degradation. When charged to high voltage (>4.5 V), lattice oxygen is over-oxidized and irreversibly escapes in the form of oxygen, causing an uncontrollable transformation of the material surface from a layered structure to a spinel phase and even a rock salt phase. The anisotropy of the lattice changes, ultimately manifesting as continuous voltage decay and rapid capacity decline during cycling.
[0004] To address this issue, related technologies have attempted to dope lithium-rich manganese-based materials with Ru, utilizing the strong Ru-O covalent bond to anchor lattice oxygen and suppress irreversible phase transitions. However, these schemes all employ a bulk uniform doping strategy, resulting in no spatial variation in Ru concentration and valence state within the particles. Chinese patent application CN120895648A relates to a lithium-rich manganese-based precursor and cathode material, its preparation method, and a battery, listing Ru as an optional doping element (alongside Zr, Ga, B, Pb, As, Ba, Ce, La, Bi, and Pt), but does not address the design of Ru concentration distribution within the particles. However, simple Ru doping fails to differentiate and enhance the regions where surface oxygen release is most severe, and uniformly doped Ru also imposes additional burdens on capacity contribution and cost control. Summary of the Invention
[0005] In view of this, this application provides a doped modified cathode material and its preparation method, as well as a lithium-ion battery. The doped modified cathode material distributes Ru at both the center and the surface, forming an increasing concentration gradient from the inside to the outside. By utilizing the strong covalent bond between Ru and O to anchor lattice oxygen, differentiated functional synergy is formed in different regions of the particle. This achieves the effect of maintaining the structure with a low concentration at the center and participating in charge compensation with a high concentration on the surface. This helps to delay the structural degradation of lithium-rich manganese-based cathode materials caused by irreversible phase transitions and oxygen escape during high-voltage cycling, and reduces the risk of voltage and capacity decay.
[0006] To achieve the above objectives, in a first aspect, this application provides a doped and modified cathode material, which includes a lithium-rich manganese-based cathode material doped with Ru. The Ru element is distributed from the center to the surface of the lithium-rich manganese-based cathode material, the particle size Dv50 of the lithium-rich manganese-based cathode material is 6 μm to 15 μm, and the concentration of Ru element increases from the center to the surface of the lithium-rich manganese-based cathode material.
[0007] Based on the first aspect, in some embodiments, the radius of the lithium-rich manganese-based cathode material is defined as R0, and the lithium-rich manganese-based cathode material is divided into three regions. The region with a distance of R1 from the center of the lithium-rich manganese-based cathode material from the center towards the surface is the first region, where 0 < R1 / R0 ≤ 30%. The region with a distance of R2 from the surface of the lithium-rich manganese-based cathode material from the surface towards the center is the third region, where 0 ≤ R2 / R0 ≤ 30%. The region in the lithium-rich manganese-based cathode material located between the first and third regions is the second region. Based on the total number of transition metal atoms in each of the first, second, and third regions, the proportion of Ru atoms in the first region is 0.5 at% to 2.0 at%, the proportion of Ru atoms in the second region is 2.0 at% to 5.0 at%, and the proportion of Ru atoms in the third region is 5.0 at% to 10.0 at%.
[0008] Based on the first aspect, in some embodiments, the Ru element in the doped and modified cathode material exists in the form of Ru... 4+ Ru 5+ and Ru 6+ In the third region, Ru 4+ It accounts for 90% or more of the total Ru moles in the region.
[0009] Based on the first aspect, in some embodiments, the Ru element in the doped and modified cathode material exists in the form of Ru... 4+ Ru 5+ and Ru 6+ After the doped and modified cathode material is first charged to ≥4.5 V, in the third region, Ru 5+ and Ru 6+ It accounts for 60% to 90% of the total Ru moles in the region.
[0010] Based on the first aspect, in some embodiments, the lithium-rich manganese-based cathode material also contains the element M, wherein M includes at least one of Zr, Mo, W, Nb and Ti.
[0011] Based on the first aspect, in some embodiments, the proportion of the amount of the element M is 0.2 mol% to 3.0 mol% based on the total amount of transition metals in the lithium-rich manganese-based cathode material doped with Ru.
[0012] Based on the first aspect, in some embodiments, the proportion of Ru element in the total amount of transition metals in the lithium-rich manganese-based cathode material doped with Ru is 3.5 mol% to 8.5 mol%.
[0013] Secondly, this application provides a method for preparing the above-mentioned doped modified cathode material, comprising the following steps: providing precursor particles of lithium-rich manganese-based cathode material; during the co-precipitation growth of the precursor particles, adding Ru source in stages, with the addition rate of Ru source increasing at each growth stage, so that the concentration of Ru element increases from the center to the surface of the precursor particles of lithium-rich manganese-based cathode material, thereby preparing an intermediate; mixing the intermediate with a lithium source, and sequentially performing a three-stage sintering process to prepare the doped modified cathode material, wherein: the first sintering is performed under a first atmosphere, and the oxygen partial pressure of the first atmosphere is 10. -4 The first sintering temperature is 550℃~650℃, and the time is 2 h~8 h; the second sintering is carried out under a second atmosphere, and the oxygen partial pressure of the second atmosphere is ≤10. -5 The second sintering is carried out at an atm temperature of 450℃~550℃ for 1 h~6 h; the third sintering is carried out under a third atmosphere with an oxygen partial pressure ≤10. -6 The temperature of the third sintering is 700℃~850℃ and the time is 4 h~12 h.
[0014] Based on the second aspect, in some embodiments, the phased addition of the Ru source includes the following steps: during the stage when the precursor particles grow to 0% to 30% of the target particle size, no Ru source is added; during the stage when the precursor particles grow to 30% to 70% of the target particle size, the Ru source is added at a rate of 0.03 mL / min to 0.08 mL / min; during the stage when the precursor particles grow to 70% to 100% of the target particle size, the Ru source is added at a rate of 0.15 mL / min to 0.25 mL / min.
[0015] Based on the second aspect, in some embodiments, the co-precipitation reaction temperature is 48°C to 52°C, and the pH is 10.3 to 10.7.
[0016] Based on the second aspect, in some implementations, the Ru source includes RuCl3.
[0017] Based on the second aspect, in some embodiments, the oxygen partial pressure in the first, second, and third atmospheres is adjusted by applying CO and CO2.
[0018] Thirdly, this application provides a lithium-ion battery comprising the aforementioned doped and modified cathode material.
[0019] Compared with traditional technologies, the beneficial effects of this application are as follows:
[0020] In the doped and modified cathode material provided in this application, Ru is distributed from the center to the surface of the lithium-rich manganese-based cathode material, and the concentration increases from the center to the surface. In related technologies, Ru only diffuses to the near-surface through the surface coating layer, the central region contains no Ru or has an extremely low Ru concentration, or Ru is uniformly distributed in the bulk phase with similar concentrations in each region. In contrast, this application achieves differentiated functional synergy in different regions of the particle by distributing Ru at both the center and the surface and forming an increasing concentration gradient from the inside to the outside. This is achieved by utilizing the strong Ru-O covalent bond to anchor lattice oxygen, resulting in Ru being distributed at both the center and the surface to maintain the integrity of the layered structure framework while avoiding lattice distortion caused by overdoping. The high Ru concentration at the surface provides stronger oxygen anchoring during electrochemical cycling to reduce the irreversible release of surface lattice oxygen. Therefore, the doped and modified cathode material provided in this application can fully utilize the functional synergy of different spatial partitions within its particles, manifested as a low concentration at the center maintaining the structure and a high concentration at the surface participating in charge compensation. This helps to delay the structural degradation of lithium-rich manganese-based cathode materials caused by irreversible phase transitions and oxygen escape during high-voltage cycling, reducing the risk of voltage and capacity decay. Simultaneously, the global distribution of Ru at the center and surface ensures the integrity of the gradient structure, which helps to solve the problem of insufficient internal structural support when there is no Ru distribution in the central region. Attached Figure Description
[0021] Figure 1 This is a schematic diagram of the structure of a doped and modified cathode material divided into a first region, a second region, and a third region, according to an embodiment of this application. Detailed Implementation
[0022] To facilitate understanding of the technical solutions of this application, a more comprehensive description of the technical solutions of this application will be provided below with reference to the accompanying drawings, which illustrate preferred embodiments of the technical solutions of this application. However, the technical solutions of this application can be implemented in many different forms and are not limited to the embodiments described herein. Rather, these embodiments are provided to enable a more thorough and comprehensive understanding of the disclosure of the technical solutions of this application.
[0023] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application belongs. The terminology used herein is for the purpose of describing particular embodiments only and is not intended to be limiting of the application. The term "and / or" as used herein includes any and all combinations of one or more of the associated listed items.
[0024] One embodiment of this application provides a doped and modified cathode material, comprising a lithium-rich manganese-based cathode material doped with Ru. The Ru element is distributed from the center to the surface of the lithium-rich manganese-based cathode material. The particle size Dv50 of the lithium-rich manganese-based cathode material is 6 μm to 15 μm, and the Ru element concentration increases from the center to the surface of the lithium-rich manganese-based cathode material. For example, the particle size Dv50 of the lithium-rich manganese-based cathode material can be 6 μm, 6.5 μm, 7 μm, 7.5 μm, 8 μm, 8.5 μm, 9 μm, 9.5 μm, 10 μm, 10.5 μm, 11 μm, 11.5 μm, 12 μm, 12.5 μm, 13 μm, 13.5 μm, 14 μm, 14.5 μm, 15 μm, or any value within the range of any two of the above values.
[0025] In the doped and modified cathode material provided in this application, Ru is distributed from the center to the surface of the lithium-rich manganese-based cathode material, and the concentration increases from the center to the surface. In related technologies, Ru only diffuses to the near-surface through the surface coating layer, the central region contains no Ru or has an extremely low Ru concentration, or Ru is uniformly distributed in the bulk phase with similar concentrations in each region. In contrast, this application achieves differentiated functional synergy in different regions of the particle by distributing Ru at both the center and the surface and forming an increasing concentration gradient from the inside to the outside. This is achieved by utilizing the strong Ru-O covalent bond to anchor lattice oxygen, resulting in Ru being distributed at both the center and the surface to maintain the integrity of the layered structure framework while avoiding lattice distortion caused by overdoping. The high Ru concentration at the surface provides stronger oxygen anchoring during electrochemical cycling to reduce the irreversible release of surface lattice oxygen. Therefore, the doped and modified cathode material provided in this application can fully utilize the functional synergy of different spatial partitions within its particles, manifested as a low concentration at the center maintaining the structure and a high concentration at the surface participating in charge compensation. This helps to delay the structural degradation of lithium-rich manganese-based cathode materials caused by irreversible phase transitions and oxygen escape during high-voltage cycling, reducing the risk of voltage and capacity decay. Simultaneously, the global distribution of Ru at the center and surface ensures the integrity of the gradient structure, which helps to solve the problem of insufficient internal structural support when there is no Ru distribution in the central region.
[0026] It should be noted that in related technologies, when the particles are large (e.g., Dv50 > 6 μm), diffusion after surface doping alone cannot effectively allow the doped elements to reach the central region. However, the doped modified cathode material of this application can achieve full-particle-range gradient doping of cathode materials with larger particle sizes (e.g., Dv50 of 6 μm to 15 μm) through in-situ co-precipitation.
[0027] In some embodiments, please refer to Figure 1The radius of the lithium-rich manganese-based cathode material is defined as R0. The lithium-rich manganese-based cathode material is divided into three regions. The region from the center to the surface, with a distance of R1 from the center of the lithium-rich manganese-based cathode material, is the first region, where 0 < R1 / R0 ≤ 30%. The region from the surface to the center, with a distance of R2 from the surface of the lithium-rich manganese-based cathode material, is the third region, where 0 ≤ R2 / R0 ≤ 30%. The region between the first and third regions is the second region. Based on the total number of transition metal atoms in each of the first, second, and third regions, the proportion of Ru atoms in the first region is 0.5 at% to 2.0 at%, the proportion of Ru atoms in the second region is 2.0 at% to 5.0 at%, and the proportion of Ru atoms in the third region is 5.0 at% to 10.0 at%. For example, the percentage of Ru atoms in the first region mentioned above can be 0.5at%, 0.6at%, 0.7at%, 0.8at%, 0.9at%, 1.0at%, 1.1at%, 1.2at%, 1.3at%, 1.4at%, 1.5at%, 1.6at%, 1.7at%, 1.8at%, 1.9at%, 2.0at%, or any value within the range of any two of the above values; the percentage of Ru atoms in the second region mentioned above can be 2.0at%, 2.25at%, 2.5at%, 2.75at%, 3 The percentage of Ru atoms in the third region can be 5.0at%, 5.5at%, 6.0at%, 6.5at%, 7.0at%, 7.5at%, 8.0at%, 8.5at%, 9.0at%, 9.5at%, 10.0at%, or any value within the range of any two of the above values. Furthermore, this application establishes a quantitative structural system with a clear concentration gradient from the center to the surface by dividing the lithium-rich manganese-based cathode material into a first region, a second region, and a third region from the inside out, and controlling the Ru concentration (in terms of Ru atomic percentage) in each region within the above range. Controlling the Ru concentration in the first region within the aforementioned range helps to provide adequate structural support in the central region, while also reducing the adverse effects of high Ru doping concentration on the long-range order of the layered structure. Controlling the Ru concentration in the second region within the aforementioned range helps to achieve a smooth transition of Ru concentration between the central and surface regions, reducing local stress concentration and structural mismatch caused by abrupt concentration changes. Controlling the Ru concentration in the third region within the aforementioned range helps to form a sufficiently high local Ru concentration in the surface region, enabling this region to provide sufficient oxygen anchoring capability to suppress lattice oxygen release during electrochemical cycling.The concentration ranges of the three regions complement each other, constructing a functionally progressive system from structural support to oxygen anchoring at the overall particle level.
[0028] In some embodiments, the Ru element in the doped cathode material exists in the form of Ru. 4+ Ru 5+ and Ru 6+ In the third region, Ru 4+ It accounts for 90% or more of the total Ru moles in the region. For example, in the third region mentioned above, Ru... 4+ The Ru content can be 90%, 91%, 92%, 93%, 94%, 95%, 96%, 97%, 98%, 99%, 99.5%, 99.9% of the total Ru molar content in the region, or any value within the range of any two of the above values. It should be noted that in the initial state after preparation, the Ru element in the doped and modified cathode material of this application is mainly in the form of Ru... 4+ The valence state exists, therefore in the third region, Ru 4+ Containing 90% or more of the total Ru molar amount in this region is beneficial for avoiding high-valence Ru ions (such as Ru...). 5+ / Ru 6+ During the material synthesis process, due to the difference between the ionic radius and Ru 4+ The lattice distortion and local internal stress caused by the differences reduce the risk of pre-damage to the initial structure of the material.
[0029] In other embodiments, the Ru element in the doped cathode material exists in the form of Ru... 4+ Ru 5+ and Ru 6+ After the doped and modified cathode material is first charged to ≥4.5 V, in the third region, Ru 5+ and Ru 6+ It accounts for 60% to 90% of the total Ru moles in this region. For example, in the aforementioned third region, Ru... 5+ and Ru 6+ The percentage of Ru molars in the region can be 60%, 63%, 66%, 69%, 72%, 75%, 78%, 81%, 84%, 87%, 90%, or any value within the range of any two of the above values. It should be noted that the doped and modified cathode material of this application, when first charged to ≥4.5 V (relative to Li), + After / Li), Ru on the surface of the cathode material 4+ Electrochemical oxidation occurs, producing Ru. 5+ and / or Ru 6+ This satisfies Ru in the third region mentioned above. 5+ and Ru 6+Within the percentage range of total Ru molars in this region, higher-valence Ru ions form stronger bonds with surrounding lattice oxygen, which is beneficial for providing a stronger anchoring effect on the lattice oxygen in the surface region under high voltage, thereby further reducing irreversible oxygen release. Simultaneously, Ru... 5+ / Ru 6+ It will be reduced back to Ru during the discharge process. 4+ The reversibility of this valence state change is beneficial for maintaining the oxygen anchoring function in subsequent cycles.
[0030] In some embodiments, the lithium-rich manganese-based cathode material further contains element M, wherein M includes at least one of Zr, Mo, W, Nb, and Ti. Furthermore, by incorporating the above-mentioned elements into the lithium-rich manganese-based cathode material, the strong covalent bond between these elements and oxygen helps to enhance the overall bonding strength of the transition metal-oxygen lattice, thereby further suppressing the activation and release of lattice oxygen under high voltage.
[0031] In some embodiments, the percentage of element M is 0.2 mol% to 3.0 mol% based on the total amount of transition metals in the Ru-doped lithium-rich manganese-based cathode material. For example, the percentage of the above-mentioned elements can be 0.2 mol%, 0.4 mol%, 0.6 mol%, 0.8 mol%, 1.0 mol%, 1.2 mol%, 1.4 mol%, 1.6 mol%, 1.8 mol%, 2.0 mol%, 2.2 mol%, 2.4 mol%, 2.6 mol%, 2.8 mol%, 3.0 mol%, or any value within the range of any two of the above values. Furthermore, controlling the total doping amount of the aforementioned co-doped elements within the above range helps to reduce the risk of structural disorder or capacity loss when the doping amount is large, while providing sufficient bonding enhancement effects.
[0032] In some embodiments, the percentage of Ru in the lithium-rich manganese-based cathode material doped with Ru is 3.5 mol% to 8.5 mol%. For example, the percentage of Ru can be 3.5 mol%, 4 mol%, 4.5 mol%, 5 mol%, 5.5 mol%, 6 mol%, 6.5 mol%, 7 mol%, 7.5 mol%, 8 mol%, 8.5 mol%, or any value within the range of any two of the above values. Furthermore, controlling the Ru doping amount within the above range is beneficial for achieving a balance between providing sufficient oxygen anchoring capability and maintaining the structural stability of the material.
[0033] An embodiment of this application also provides a method for preparing the above-mentioned doped and modified cathode material, comprising the following steps:
[0034] Step 1: Provide precursor particles for lithium-rich manganese-based cathode materials.
[0035] In some embodiments, the precursor particles have the general chemical formula Mn a Ni b (OH)₂, wherein 0.6 ≤ a ≤ 0.75, 0.25 ≤ b ≤ 0.4, and a + b = 1. For example, the chemical formula of the precursor particles can be Ni. 0.25 Mn 0.75 (OH)2.
[0036] In other embodiments, when it is necessary to introduce co-doping elements M such as Zr, Mo, W, Nb, and Ti, the general chemical formula of the precursor particles is Mn. a Ni b M 1-a-b (OH)₂, where 0.6 ≤ a ≤ 0.75, 0.25 ≤ b ≤ 0.4, and a + b = 1. Understandably, Mn a Ni b M 1-a-b The preparation method of (OH)2 precursor includes: mixing an M source (such as Zr(SO4)2, (NH4)2MoO4, TiOSO4, Nb2(C2O4)5, Na2WO4, etc.) with a Ni source and an Mn source, and then obtaining the precursor through a co-precipitation reaction. Understandably, during the co-precipitation reaction, the mixed salt solution containing Ni, Mn, and the M source is continuously injected into the reactor at a constant flow rate, allowing the M element to precipitate simultaneously with the Ni and Mn elements, and also contributing to the uniform bulk doping of the M element in the precursor particles.
[0037] Step 2: During the co-precipitation growth of precursor particles, Ru source is added in stages, and the addition rate of Ru source increases in each growth stage, so that the concentration of Ru element increases from the center to the surface of the precursor particles of lithium-rich manganese-based cathode material, thus preparing intermediate.
[0038] In the above steps, by adding Ru source in stages during the precursor co-precipitation growth process and controlling the increasing rate of Ru source addition at each growth stage, the Ru element actively constructs an increasing concentration distribution from the center to the surface inside the precursor. Compared with the related technology of first synthesizing the precursor or oxide and then diffusing the dopant element from the surface to the inside through solution impregnation, the method of this application can embed Ru in situ into the lattice of each region during particle growth, avoiding the limitation of the post-processing infiltration method where the dopant element can only penetrate into the near-surface region and cannot be effectively doped in the central region, while ensuring the synchronous matching of the concentration gradient and the particle growth process.
[0039] In some embodiments, the staged addition of the Ru source includes the following steps: during the stage when the precursor particles grow to 0% to 30% of the target particle size, no Ru source is added; during the stage when the precursor particles grow to 30% to 70% of the target particle size, the Ru source is added at a rate of 0.03 mL / min to 0.08 mL / min; during the stage when the precursor particles grow to 70% to 100% of the target particle size, the Ru source is added at a rate of 0.15 mL / min to 0.25 mL / min. For example, during the stage where precursor particles grow to 30%–70% of the target particle size, the Ru source addition rate can be 0.03 mL / min, 0.035 mL / min, 0.04 mL / min, 0.045 mL / min, 0.05 mL / min, 0.055 mL / min, 0.06 mL / min, 0.065 mL / min, 0.07 mL / min, 0.075 mL / min, 0.08 mL / min, or any value within the range of any two of the above values; during the stage where precursor particles grow to 70%–100% of the target particle size, the Ru source addition rate can be 0.15 mL / min, 0.16 mL / min, 0.17 mL / min, 0.18 mL / min, 0.19 mL / min, 0.20 mL / min, 0.21 mL / min, 0.22 mL / min, 0.23 mL / min, 0.24 mL / min, 0.25 mL / min, or any value within the range of any two of the above values. mL / min or any value within the range of any two of the above values.
[0040] Furthermore, not adding a Ru source during the 0%–30% growth stage of the precursor particles to the target particle size helps maintain a low Ru concentration in the central region of the precursor particles, thus preserving the integrity of the layered structure framework. During the 30%–70% growth stage, the Ru source addition rate is within this range, which helps form a gentle concentration transition layer in the middle region of the precursor particles, reducing structural stress caused by abrupt concentration changes between the center and surface. During the 70%–100% growth stage, the Ru source addition rate is within this range, which helps achieve higher local Ru enrichment on the surface of the precursor particles, enhancing the anchoring ability of this region to lattice oxygen. The feeding rates in these three stages are coordinated to create a continuous distribution of Ru concentration with a gradient increasing along the radial direction of the particles. It should be noted that during the 0%–30% stage, no Ru source is actively added; instead, the Ru in the co-precipitation reaction system is utilized… 3+ With OH -The Ru(OH)3 generated in the reaction is uniformly dispersed in the Ni-Mn hydroxide matrix in the form of nanoscale coprecipitation. In the subsequent stage, the Ru source added generates Ru(OH)3 that precipitates on the surface of the existing particles. As the precursor particles continue to grow, some Ru ions can enter the particle interior through the surface adsorption-recrystallization mechanism under the dynamic equilibrium of the coprecipitation system, thereby realizing the distribution of Ru in the central region.
[0041] In some embodiments, the coprecipitation reaction temperature is 48℃~52℃, and the pH is 10.3~10.7. For example, the coprecipitation reaction temperature can be 48℃, 48.4℃, 48.8℃, 49.2℃, 49.6℃, 50℃, 50.4℃, 50.8℃, 51.2℃, 51.6℃, 52℃, or any value within any two of the above values; the coprecipitation pH can be 10.3, 10.4, 10.5, 10.6, 10.7, or any value within any two of the above values. Furthermore, controlling the coprecipitation reaction temperature and pH within the above ranges helps ensure the consistency of the precursor particle growth rate and the uniform coprecipitation of Ru(OH)3 in the precursor, thereby facilitating the achievement of a stable gradient doped structure.
[0042] In some embodiments, the Ru source includes RuCl3. Furthermore, because RuCl3 has good solubility in water, it can form stable Ru... 3+ Ionic solutions are advantageous for achieving uniform molecular-scale dispersion of ruthenium in coprecipitation reaction systems. Simultaneously, Ru in RuCl3... 3+ Under alkaline conditions (pH=10.5±0.2) in the coprecipitation system, Ru(OH)3 can react to form an insoluble precipitate, which has similar solubility product and precipitation kinetics characteristics to Ni-Mn hydroxide. This is beneficial for achieving uniform coprecipitation of Ru(OH)3 and Ni-Mn hydroxide, allowing Ru to be deposited synchronously with the matrix material during the in-situ growth of precursor particles, thereby reducing phase separation or local enrichment due to differences in precipitation rates.
[0043] Step 3: The intermediate is mixed with the lithium source and subjected to a three-stage sintering process to prepare the doped and modified cathode material. The first sintering is performed under a first atmosphere with an oxygen partial pressure of 10. -4 The first sintering temperature is 550℃~650℃, and the time is 2 h~8 h; the second sintering is carried out under a second atmosphere, and the oxygen partial pressure of the second atmosphere is ≤10. -5 The second sintering is carried out at an atm temperature of 450℃~550℃ for 1 h~6 h; the third sintering is carried out under a third atmosphere with an oxygen partial pressure ≤10. -6The temperature of the third sintering is 700℃~850℃ and the time is 4 h~12 h. For example, the first sintering temperature can be 550℃, 560℃, 570℃, 580℃, 590℃, 600℃, 610℃, 620℃, 630℃, 640℃, 650℃, or any value within the range of any two of the above values; the first sintering time can be 2 h, 2.5 h, 3 h, 3.5 h, 4 h, 4.5 h, 5 h, 5.5 h, 6 h, 6.5 h, 7 h, 7.5 h, 8 h, or any value within the range of any two of the above values; the second sintering temperature can be 450℃, 460℃, 470℃, 480℃, 490℃, 500℃, 510℃, 520℃, 530℃, 540℃, 550℃, or any value within the range of any two of the above values; the second sintering time can be 1 h, 1.5 h, 2 h, 2.5 h, 3 h, 3.5 h, 4 h, 4.5 h. The sintering time can be 700℃, 715℃, 730℃, 745℃, 760℃, 775℃, 790℃, 805℃, 820℃, 835℃, 850℃ or any value within the range of any two values above; the sintering temperature can be 4 h, 4.8 h, 5.6 h, 6.4 h, 7.2 h, 8 h, 8.8 h, 9.6 h, 10.4 h, 11.2 h, 12 h or any value within the range of any two values above.
[0044] In the above steps, the gradient distribution and material structure are synergistically controlled through three sequential sintering processes: the first sintering is carried out in a medium-temperature oxidizing atmosphere, which helps the precursor to initially crystallize and form a layered structural framework, while simultaneously allowing the Ru in the precursor to... 3+ Start to Ru 4+ The first sintering stage involves a conversion process; the second sintering is performed at a lower temperature and under a low oxygen partial pressure atmosphere, which helps to control the local migration behavior of Ru ions under low oxygen partial pressure conditions while avoiding over-sintering, thereby further widening the concentration difference between the central and surface regions; the third sintering stage is performed under a reducing atmosphere with an even lower oxygen partial pressure, which helps to achieve the target crystallinity of the material, fixing Ru in a stable +4 valence state in the crystal lattice, while avoiding the formation of Ru oxides, thus ensuring that Ru exists in the bulk crystal lattice in a gradient doping form. The synergistic combination of temperature, time, and oxygen partial pressure conditions in the three sintering stages allows the Ru concentration gradient distribution to be maintained and fixed during the material crystallization process, thereby obtaining a cathode material with a predetermined doping distribution.
[0045] In some embodiments, the partial pressure of oxygen in the first, second, and third atmospheres is adjusted by applying CO and CO2. Furthermore, since there is a reaction equilibrium between CO and CO2 at high temperatures (2CO + O2 → 2CO2 and 2CO2 → 2CO + O2), the partial pressure ratio of CO to CO2 can be adjusted using this chemical equilibrium to precisely regulate the partial pressure of oxygen in the atmosphere. The adjustment range can cover conditions ranging from strongly reducing atmospheres (oxygen partial pressure below 10) to atmospheres with oxygen partial pressures below 10. -5 (atm) weakly reducing (oxygen partial pressure 10) -2 atm~10 -4 The range of CO and CO2 atmospheres is from atm to oxidizing (air or pure oxygen atmosphere). Compared to adjusting the oxygen partial pressure by diluting air or oxygen with inert gases, CO and CO2 atmospheres have reducing properties, which is beneficial for controlling the valence state and migration behavior of Ru ions during the second sintering process. Compared to directly using strong reducing gases such as H2, the reducing properties of CO and CO2 gas pairs are relatively mild, which helps to reduce the risk of irreversible damage to the layered structure of the cathode material when the reducing activity is strong.
[0046] One embodiment of this application also provides a lithium-ion battery comprising the above-described doped and modified cathode material.
[0047] In the lithium-ion battery of this application, since Ru is distributed from the center to the surface of the doped and modified cathode material with increasing concentration and a specific valence spatial distribution, the lithium-ion battery containing this cathode material benefits from the spatial partitioning management of structural stability and oxygen anchoring ability brought about by Ru gradient doping during high-voltage cycling, thereby facilitating the achievement of better cycle capacity retention and voltage retention.
[0048] The present application will be described below through specific embodiments and comparative examples. Those skilled in the art should understand that the preparation methods described in this application are merely examples, and any other suitable preparation methods are within the scope of this application.
[0049] Example 1:
[0050] A doped and modified cathode material is prepared by the following method:
[0051] Step 1, Precursor Preparation: Ni was prepared using a co-precipitation method. 0.25 Mn 0.75 (OH)₂ precursor. A mixed solution of NiSO₄·6H₂O and MnSO₄·H₂O with a total concentration of 2 mol / L was prepared, with a molar ratio of Ni:Mn = 1:3. This mixed solution was continuously injected into the reactor at a rate of 2 mL / min. The coprecipitation reaction was carried out under a nitrogen atmosphere, with the reaction temperature controlled at 50℃, the pH value controlled at 10.5 by adding NaOH solution dropwise, and the stirring rate at 250 rpm. The total reaction time was approximately 12 hours.
[0052] The second step involves adding the Ru source in stages: preparing a 0.2 mol / L RuCl3 solution, with Ru added as Ru... 3+ It exists in the form of [the precursor particles]. During the coprecipitation reaction, RuCl3 solution is added in stages according to the growth process of the precursor particles: in the first stage (particle growth from 0% to 30% of particle size), no RuCl3 solution is added; in the second stage (particle growth from 30% to 70% of particle size), RuCl3 solution is added at a rate of 0.05 mL / min; in the third stage (particle growth from 70% to 100% of particle size), RuCl3 solution is added at a rate of 0.20 mL / min.
[0053] The third step is lithium mixing: the precursor containing Ru gradient distribution is mixed with LiOH·H2O in a ball mill jar at a molar ratio of Li:(Ni+Mn+Ru)=1.5:1, and the ball milling rate is 200 rpm for 2 hours.
[0054] Step 4, Atmosphere Calcination Heat Treatment: The mixture is placed in a controlled atmosphere tube furnace and sintered in the following stages: First sintering: heating to 600℃ at 5℃ / min, air atmosphere (oxygen partial pressure 0.21 atm), holding for 4 hours; cooling to 500℃ at 3℃ / min, while simultaneously switching the gas source to CO / CO2 regulated oxygen partial pressure (≤10). -5 atm); second sintering, held at 500℃ for 3 hours, oxygen partial pressure <10 -5 atm (adjusted via CO / CO2); increase temperature to 800℃ at 3℃ / min, then switch the gas source to a reducing atmosphere (PO2=10). -6 atm); third sintering, held at 800℃ for 8 hours, reducing atmosphere (PO2=10). -6 atm).
[0055] Step 5, cooling: Cool to room temperature at a rate of 20℃ / min to obtain the doped and modified cathode material.
[0056] Example 2:
[0057] The difference from Example 1 is that the coprecipitation temperature was adjusted to 48°C and the pH was adjusted to 10.7; the RuCl3 addition rate was adjusted to 0.03 mL / min in the second stage and 0.15 mL / min in the third stage; the sintering conditions were adjusted as follows: the oxygen partial pressure in the first sintering was adjusted to 1 atm, the temperature was adjusted to 550°C and the time was adjusted to 8 h; the temperature in the second sintering was adjusted to 450°C and the time was adjusted to 6 h; and the temperature in the third sintering was adjusted to 700°C and the time was adjusted to 12 h.
[0058] Example 3:
[0059] The difference from Example 1 is that the coprecipitation temperature was adjusted to 52°C and the pH was adjusted to 10.3; the RuCl3 addition rate was adjusted to 0.08 mL / min in the second stage and 0.25 mL / min in the third stage; and the sintering conditions were adjusted, with the oxygen partial pressure in the first sintering stage adjusted to 10. -4 The temperature was adjusted to 650℃ and the time to 2 h for the first sintering, the temperature was adjusted to 550℃ and the time to 1 h for the second sintering, and the temperature was adjusted to 850℃ and the time to 4 h for the third sintering.
[0060] Example 4:
[0061] The difference from Example 1 is that, when preparing the mixed solution of NiSO4·6H2O and MnSO4·H2O, Zr(SO4)2 was additionally dissolved in the mixed solution, so that the molar percentage of Zr element relative to the total amount of Ni+Mn+Zr was 1 mol%. Throughout the coprecipitation reaction, the mixed salt solution containing Ni, Mn, and Zr was continuously injected into the reactor at the same rate (2 mL / min) as in Example 1 until the reaction was complete, thereby ensuring a uniform distribution of Zr element within the precursor particles. The method of adding the RuCl3 solution and the segmented sintering process were consistent with Example 1.
[0062] Example 5:
[0063] The difference from Example 1 is that when preparing the mixed solution of NiSO4·6H2O and MnSO4·H2O, (NH4)2MoO4 is additionally dissolved in the mixed solution, so that the molar percentage of Mo relative to the total amount of Ni+Mn+Mo is 1 mol%. Throughout the coprecipitation reaction, this mixed salt solution containing Ni, Mn, and Mo is continuously injected into the reactor at the same rate (2 mL / min) as in Example 1 until the reaction is complete, thereby ensuring a uniform distribution of Mo within the precursor particles. The method of adding the RuCl3 solution and the segmented sintering process are consistent with Example 1.
[0064] Example 6:
[0065] The difference from Example 1 is that, when preparing the mixed solution of NiSO4·6H2O and MnSO4·H2O, TiOSO4 was additionally dissolved in the mixed solution, so that the molar percentage of Ti element relative to the total amount of Ni+Mn+Ti was 1 mol%. Throughout the coprecipitation reaction, the mixed salt solution containing Ni, Mn, and Ti was continuously injected into the reactor at the same rate (2 mL / min) as in Example 1 until the reaction was complete, thereby ensuring a uniform distribution of Ti element within the precursor particles. The method of adding RuCl3 solution and the segmented sintering process were consistent with Example 1.
[0066] Example 7:
[0067] The difference from Example 1 is that, when preparing the mixed solution of NiSO4·6H2O and MnSO4·H2O, Nb2(C2O4)5 was additionally dissolved in the mixed solution, so that the molar percentage of Nb element relative to the total amount of Ni+Mn+Nb was 0.2 mol%. Throughout the coprecipitation reaction, the mixed salt solution containing Ni, Mn, and Nb was continuously injected into the reactor at the same rate (2 mL / min) as in Example 1 until the reaction was complete, thereby ensuring a uniform distribution of Nb element within the precursor particles. The method of adding RuCl3 solution and the segmented sintering process were consistent with Example 1.
[0068] Example 8:
[0069] The difference from Example 1 is that, when preparing the mixed solution of NiSO4·6H2O and MnSO4·H2O, Na2WO4 was additionally dissolved in the mixed solution, so that the molar percentage of W element relative to the total amount of Ni+Mn+W was 3 mol%. Throughout the coprecipitation reaction, this mixed salt solution containing Ni, Mn, and W was injected into the reactor at the same rate (2 mL / min) as in Example 1 until the reaction was complete, thereby ensuring a uniform distribution of W element within the precursor particles. The method of adding RuCl3 solution and the segmented sintering process were consistent with Example 1.
[0070] Comparative Example 1:
[0071] The difference from Example 1 is that, in the co-precipitation growth of the precursor particles, RuCl3 is added uniformly all at once during the initial stage of the reaction, instead of being added in stages; simultaneously, in the staged sintering, sintering is first carried out at 800°C in an air atmosphere and held for 3 hours, and then an oxygen partial pressure (≤10) adjusted by CO / CO2 is applied. -5 (atm), continue sintering at 800℃ and hold for 5 h.
[0072] Comparative Example 2:
[0073] The difference from Example 1 is that the method of introducing Ru element is changed from "adding it in stages during the co-precipitation process" to "first synthesizing a lithium-rich manganese-based cathode material without Ru, and then introducing Ru through surface impregnation": that is, first Ni 0.25 Mn 0.75 (OH)2 precursor and LiOH·H2O were mixed at a molar ratio of Li:(Ni+Mn)=1.5:1 and heated to 800℃ for 10 h in air at a rate of 5℃ / min to obtain a Ru-free lithium-rich manganese-based cathode material matrix. The matrix material was dispersed in a 0.2 mol / L RuCl3 solution (solid-liquid ratio of 1:4, g / mL), stirred and impregnated at room temperature for 8 h, evaporated to dryness at 80℃, and then subjected to high-temperature diffusion treatment at 800℃ for 6 h in air at a rate of 5℃ / min to diffuse the Ru adsorbed on the surface into the particle interior, thus obtaining a surface-doped modified cathode material.
[0074] Comparative Example 3:
[0075] The difference from Example 1 is that, in the first stage (particle growth from 0% to 30% of particle size), RuCl3 solution is added at a rate of 0.015 mL / min; in the second stage (particle growth from 30% to 70% of particle size), RuCl3 solution is added at a rate of 0.025 mL / min; and in the third stage, the rate of addition of RuCl3 solution remains unchanged, so that the total amount of RuCl3 solution added is consistent with that in Example 1.
[0076] Comparative Example 4:
[0077] The difference from Example 1 is that the atmosphere in the second sintering (i.e. the second atmosphere) is adjusted to an oxygen partial pressure of 1 atm, and a CO / CO2 reducing atmosphere is not used.
[0078] The testing method for this application is as follows:
[0079] 1. Spatial distribution characterization of Ru concentration: High-angle annular dark-field scanning transmission electron microscopy combined with energy dispersive spectroscopy (EDS) in line scan mode was used to perform multi-point analysis along the radial direction of the particles. Sampling points were set at equal intervals from the particle center to the surface, with at least 10 sampling points, and at least 3 EDS spectra were collected at each sampling point, with the average value taken. The concentration was calculated as the atomic percentage of Ru with the total number of transition metal atoms (Ni + Mn + Ru + other possible co-doping elements) as 100%. The bulk average Ru doping amount x was calculated based on the line scan data.
[0080] 2. Characterization of the initial Ru valence state: The valence state of Ru in the prepared sample was analyzed using X-ray photoelectron spectroscopy. Ru 3p was collected. 3 / 2 Core level spectrum (Ru 4+(Referencing a peak at approximately 462 eV), the Ru content of Ru in the initial state (i.e., before charge-discharge cycling) was confirmed by comparison with a standard RuO2 sample. 4+ The percentage of molar content in valence state.
[0081] 3. Characterization of Ru valence state after the first charge: The assembled coin cell was first charged to 4.8 V (relative to Li) at a 0.1 C rate. + The battery was carefully disassembled in an Ar-filled glove box, and the positive electrode was removed. The positive electrode was washed three times with anhydrous DMC (dimethyl carbonate) solvent to remove residual electrolyte. After vacuum drying, the positive electrode material powder was scraped off and subjected to XPS analysis. Ru 3p was analyzed. 3 / 2 The peak fitting results of the spectrum confirm Ru 5+ (Approximately 464 eV) and / or Ru 6+ The characteristic peak (approximately 466 eV) yields Ru 5+ and Ru 6+ The molar content percentage of Ru. Samples discharged to 2.0 V were prepared using the same method to verify Ru. 5+ / Ru 6+ Restored to Ru 4+ The process.
[0082] 4. Electrochemical performance testing:
[0083] (1) Battery assembly: The positive electrode material was mixed with Super P conductive carbon black and PVDF (polyvinylidene fluoride) in NMP (N-methylpyrrolidone) at a mass ratio of 8:1:1 to form a slurry, which was then coated onto aluminum foil and dried in a vacuum oven at 120°C for 12 hours to form the positive electrode sheet. The negative electrode was a lithium metal sheet, the separator was Celgard 2325, and the electrolyte was 1 M LiPF6 dissolved in a mixed solvent of EC / DMC / EMC (volume ratio 1:1:1). CR2032 coin cells were assembled in an Ar atmosphere glove box (H2O < 0.1 ppm, O2 < 0.1 ppm).
[0084] (2) The constant current charge-discharge test voltage range is 2.0 V~4.8 V (vs. Li + / Li). During the first charge, Ru 4+ Electrochemical oxidation to Ru 5+ / Ru 6+Spontaneous generation, requiring no additional pretreatment or special charging regime. Before cycling, the cells were activated for 3 cycles at a rate of 0.1C (1C = 250 mA / g), followed by constant current charge-discharge tests at specified rates (0.5C, 1C, 2C, 5C). Voltage decay was determined by calculating the median voltage drop per 50 discharge cycles, in mV / cycle. At least three parallel cells were used for each example / comparative test, and the average value was taken. All tests were conducted under isothermal conditions of 25±2℃.
[0085] Please refer to Table 1 for a comparison of the preparation conditions in Examples 1-8 of this application, and please refer to Tables 2 and 3 for the test results mentioned above.
[0086] Table 1. Some preparation conditions of Examples 1-8 of this application
[0087]
[0088] Table 2 Performance test results of the doped modified cathode materials obtained in Examples 1-8 and Comparative Examples 1-4 of this application
[0089]
[0090] Table 3. Electrochemical performance test results of the coin cells obtained in Examples 1-8 and Comparative Examples 1-4 of this application.
[0091]
[0092] Please refer to Table 1. In the doped and modified cathode materials provided in Examples 1-8 of this application, Ru is distributed from the center to the surface of the lithium-rich manganese-based cathode material, and the concentration increases from the center to the surface. By distributing Ru at both the center and the surface and forming an increasing concentration gradient from the inside to the outside, the strong Ru-O covalent bond anchors lattice oxygen, creating differentiated functional synergies in different regions of the particle: the low concentration of Ru near the center maintains the integrity of the layered structure framework while avoiding lattice distortion caused by overdoping, while the high concentration of Ru on the surface provides stronger oxygen anchoring during electrochemical cycling to reduce irreversible release of surface lattice oxygen. Thus, the doped and modified cathode materials provided in Examples 1-8 of this application can fully utilize the functional synergy of different spatial partitions within the particle, manifested as a low concentration at the center maintaining the structure and a high concentration on the surface participating in charge compensation. This helps to delay the structural degradation of the lithium-rich manganese-based cathode material caused by irreversible phase transitions and oxygen escape during high-voltage cycling, reducing the risk of voltage and capacity decay. Meanwhile, the global distribution of Ru at the center and surface ensures the integrity of the gradient structure, which helps to solve the problem of insufficient internal structural support when there is no Ru distribution in the central region. Among them, Examples 4-8 are further doped with Zr, Mo, W, Nb and Ti as synergistic dopants. The strong covalent bond between these elements and oxygen helps to enhance the overall bonding strength of the transition metal-oxygen lattice, thereby further suppressing the activation and release of lattice oxygen under high voltage.
[0093] Referring to Tables 2 and 3, the capacity retention rate of Examples 1-8 of this application after 300 cycles at 1C all reached over 88% (88.2%~93.8%), the voltage decay was controlled below 0.51 mV / cycle (0.31~0.51 mV / cycle), and the specific capacity at 5C rate all reached over 203 mAh / g (203.8~216.5 mAh / g). This indicates that by constructing a gradient distribution of Ru concentration from the center to the surface within the particles, the low Ru concentration in the central region helps maintain the integrity of the layered structure framework and avoids lattice distortion caused by excessive doping; while the high Ru concentration in the surface region is beneficial for the passage of Ru through the surface during electrochemical cycling. 4+ / Ru 5+ / Ru 6+The reversible valence state change provides a stronger oxygen anchoring effect to suppress the irreversible release of oxygen from the surface lattice; the synergistic effect of the two enables spatial partitioning management within the particles, thus achieving better cycle stability and voltage retention than the comparative examples within a wider process parameter window. Based on Examples 1-3, Examples 4-8 show a further optimization trend in electrochemical performance, with capacity retention of over 92% (92.3%~93.8%) after 300 cycles at 1C, and over 88% (88.2%~90.5%) after 500 cycles, while voltage decay is controlled below 0.36 mV / cycle (0.31~0.36 mV / cycle). This indicates that the introduction of co-doped elements and Ru gradient doping form an effective synergistic enhancement effect.
[0094] Compared to Example 1 of this application, in the preparation process of Comparative Example 1, the Ru source was added uniformly all at once during the initial stage of co-precipitation, without a staged addition scheme. This resulted in a more uniform distribution of Ru in the particles (no significant difference in Ru concentration from the first region to the third region), failing to form an increasing gradient from the center to the surface. Because a high concentration of Ru failed to accumulate on the surface, the Ru generated in situ on the surface during the first charge... 5+ / Ru 6+ The quantity is insufficient to fully suppress the irreversible release of surface lattice oxygen, resulting in poor cycle stability and voltage retention.
[0095] Compared to Example 1 of this application, in the preparation process of Comparative Example 2, the method of introducing Ru was changed from "in-situ staged doping during co-precipitation" to "first synthesizing a Ru-free matrix material, and then introducing Ru through surface impregnation combined with high-temperature diffusion". This post-treatment method resulted in Ru being enriched only in the shallow region of the particle surface, while the central and intermediate regions were basically free of Ru (the Ru concentration in the first and second regions was 0). Due to the lack of structural support from Ru in the central region, the layered structure inside the particle would gradually deteriorate during long-term cycling, and therefore its long-cycle retention rate (especially after 500 cycles) was significantly lower than that of Example 1.
[0096] Compared to Example 1 of this application, in the preparation process of Comparative Example 3, RuCl3 solution was also added in the first stage (0%~30% particle size). Although the rate was controlled at a low level, it still resulted in a higher Ru concentration in the central region. Excessive doping in the central region led to a higher Ru concentration. 4+ (Ionic radius 0.62 Å) for Mn 4+ The excessive substitution ratio of (ionic radius 0.53 Å) caused lattice distortion and internal stress accumulation, which adversely affected the long-range order of the layered structure. Therefore, its cycling stability and rate performance were not as good as those of Example 1.
[0097] Compared to Example 1 of this application, in the preparation process of Comparative Example 4, the second sintering stage did not use a low oxygen partial pressure CO / CO2 reducing atmosphere, but was carried out in an oxidizing atmosphere with an oxygen partial pressure of 1 atm. This resulted in some Ru being over-oxidized to a high oxidation state (Ru) in the prepared state. 5+ / Ru 6+ ), preparation of Ru 4+ The proportion of high-valence Ru ions is significantly lower than in Example 1. High-valence Ru ions introduce local distortion and internal stress into the initial structure of the material, leading to a significant decrease in the initial coulombic efficiency and accelerating structural collapse in subsequent cycles. Therefore, its cycle retention rate and voltage retention capability are inferior to those of Example 1. The results of Comparative Example 4 also illustrate the necessity of the low oxygen partial pressure condition in the second sintering stage of this application, which ensures that the prepared Ru is in the form of Ru... 4+ The form is stable in the crystal lattice, avoiding pre-damage to the initial structure of the material, and allowing the valence state change of Ru to occur controllably during the electrochemical process.
[0098] The technical features of the above embodiments can be combined in any way. For the sake of brevity, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0099] The embodiments described above are merely illustrative of several implementations of the technical solution of this application, and while the descriptions are specific and detailed, they should not be construed as limiting the scope of the technical solution of this application. It should be noted that those skilled in the art can make various modifications and improvements without departing from the inventive concept of this application, and these modifications and improvements all fall within the protection scope of this application. Therefore, the protection scope of this application should be determined by the appended claims.
Claims
1. A doped and modified cathode material, characterized in that, The doped and modified cathode material includes a lithium-rich manganese-based cathode material doped with Ru. The Ru element is distributed from the center to the surface of the lithium-rich manganese-based cathode material particles. The particle size Dv50 of the lithium-rich manganese-based cathode material particles is 6 μm to 15 μm, and the concentration of the Ru element increases from the center to the surface of the lithium-rich manganese-based cathode material particles.
2. The doped and modified cathode material as described in claim 1, characterized in that, The radius of the lithium-rich manganese-based cathode material is defined as R0. The lithium-rich manganese-based cathode material is divided into three regions. The region with a distance of R1 from the center of the lithium-rich manganese-based cathode material from the center towards the surface is the first region, where 0 < R1 / R0 ≤ 30%. The region with a distance of R2 from the surface of the lithium-rich manganese-based cathode material from the surface towards the center is the third region, where 0 ≤ R2 / R0 ≤ 30%. The region of the lithium-rich manganese-based cathode material located between the first region and the third region is the second region. Based on the total number of transition metal atoms in each of the first, second, and third regions, the proportion of Ru atoms in the first region is 0.5at% to 2.0at%, the proportion of Ru atoms in the second region is 2.0at% to 5.0at%, and the proportion of Ru atoms in the third region is 5.0at% to 10.0at.
3. The doped and modified cathode material as described in claim 2, characterized in that, The Ru element in the doped and modified cathode material exists in the form of Ru. 4+ Ru 5+ and Ru 6+ The doped and modified cathode material satisfies at least one of the following conditions: (1) In the third region, Ru 4+ It accounts for 90% or more of the total Ru moles in the region; (2) After the doped and modified cathode material is first charged to ≥4.5 V, in the third region, Ru 5+ and Ru 6+ It accounts for 60% to 90% of the total Ru moles in the region.
4. The doped and modified cathode material as described in claim 1, characterized in that, The lithium-rich manganese-based cathode material also contains the element M, wherein M includes at least one of Zr, Mo, W, Nb and Ti.
5. The doped and modified cathode material as described in claim 4, characterized in that, Based on the total amount of transition metals in the lithium-rich manganese-based cathode material doped with Ru, the amount of M is 0.2 mol% to 3.0 mol%.
6. The doped and modified cathode material as described in claim 1, characterized in that, Based on the total amount of transition metals in the lithium-rich manganese-based cathode material doped with Ru, the amount of Ru is 3.5 mol% to 8.5 mol%.
7. A method for preparing the doped and modified cathode material as described in claim 1, characterized in that, Includes the following steps: Provides precursor particles for lithium-rich manganese-based cathode materials; During the co-precipitation growth of the precursor particles, a Ru source is added in stages, and the addition rate of the Ru source increases in each growth stage, so that the concentration of Ru element increases from the center to the surface of the precursor particles of the lithium-rich manganese-based cathode material, thus preparing an intermediate. The intermediate is mixed with a lithium source and subjected to a three-stage sintering process to prepare the doped and modified cathode material, wherein: The first sintering is carried out under a first atmosphere, the oxygen partial pressure of which is 10. -4 The temperature of the first sintering is 550℃~650℃, and the time is 2 h~8 h. The second sintering is carried out under a second atmosphere, wherein the oxygen partial pressure of the second atmosphere is ≤10. -5 atm, the second sintering temperature is 450℃~550℃, and the time is 1 h~6 h; The third sintering is carried out under a third atmosphere, wherein the oxygen partial pressure of the third atmosphere is ≤10. -6 The third sintering temperature is 700℃~850℃ and the time is 4 h~12 h.
8. The preparation method according to claim 7, characterized in that, The phased addition of the Ru source includes the following steps: During the stage when the precursor particles grow to 0%~30% of the target particle size, no Ru source is added; During the stage when the precursor particles grow to 30%~70% of the target particle size, the Ru source is added at a rate of 0.03 mL / min~0.08 mL / min; During the stage when the precursor particles grow to 70% to 100% of the target particle size, the Ru source is added at a rate of 0.15 mL / min to 0.25 mL / min.
9. The preparation method according to claim 7, characterized in that, The preparation method satisfies at least one of the following conditions: (1) The reaction temperature of the coprecipitation is 48℃~52℃, and the pH is 10.3~10.7; (2) The Ru source includes RuCl3; (3) The oxygen partial pressure in the first, second and third atmospheres is adjusted by applying CO and CO2.
10. A lithium-ion battery, characterized in that, The lithium-ion battery includes a doped and modified cathode material as described in any one of claims 1-6.
Citation Information
Patent Citations
Lithium-rich manganese-based precursor, lithium-rich manganese-based positive electrode material, preparation method thereof and battery
CN120895648A